Optimization of compression formulation and load of food-grade tracers for grain traceability using central composite design - Kun, Liang; Lingling, Zhang; Wei, Lu; Okinda, Cedric Sean; Mingxia, Shen (International Journal of Agricultural and Biological Engineering, 2017)
Food-grade tracers have been developed as an identification technology for grain traceability from original harvest to final destination for transportation. The characteristics of food-grade tracers must be able to satisfy the environmental demands for grain traceability. To optimize the food-grade tracer production process, the effects of direct compression formulation and load on the mechanical characteristics were studied using response surface methodology (RSM) with central composite design (CCD). Among the four tested formulations, Formulations #2 (consisting of 35.00% lactose 100 mesh, 64.50% microcrystalline cellulose 102 and 0.50% magnesium stearate) and #4 (consisting of 38.00% lactose 100 mesh, 50.00% microcrystalline cellulose 102, 11.00% pregelatinized starch and 1.00% magnesium stearate) were selected for tracer production based on their physical properties as powders. The value of Carr’s flowability index was 68 for both Formulations #2 and #4, which was the highest among all the formulations. Therefore, Formulations #2 and #4 also had the best powder flowability. The magnesium stearate ratio (1.00%-3.00%) and pressure (6.00-16.00 kgf) were used as independent variables to detect changes in the breaking rate, peak shear force and friction coefficient of tracers compressed by the selected formulations. The optimal production parameters could be achieved at a magnesium stearate ratio of 2.25% and pressure of 16.00 kgf for Formulation #2 and at a magnesium stearate ratio of 1.02% and pressure of 16.00 kgf for Formulation #4. Under these optimal conditions, the tracers had good impact characteristics (breaking rate), compression characteristics (peak shear force) and frictional characteristics (friction coefficient). Moreover, Formulation #2 was more suitable for production because compared to Formulation #4, its breaking rate and friction coefficient values were lower, and its peak shear force value was higher.Keywords: grain traceability, food-grade tracer, optimization, food safety, formulation, mechanical property, central composite designDOI: 10.25165/j.ijabe.20171006.3531Citation: Liang K, Zhang L L, Lu W, Okinda C S, Shen M X. Optimization of compression formulation and load of food-grade tracers for grain traceability using central composite design. Int J Agric & Biol Eng, 2017; 10(6): 221–230.